Rekrutmen Tenaga Pendidik dalam Peningkatan Mutu Pendidikan di Pondok Pesantren Musthafawiyah Purbabaru - Yusuf Hadijaya, Inom Nasution, Ariani, (Universitas Islam Negeri Sumatera Utara Medan, 2020)
This study aims to describe the process of recruiting educators at the Mustahafawiyah Purbabaru Islamic Boarding School, which focuses on the recruitment process in improving the quality of education, obstacles that arise and solutions offered during the recruitment process. This research uses qualitative research with a qualitative descriptive approach. The purpose of this study was to determine how the recruitment of educators at the Mustahafawiyah Purbabaru Islamic Boarding School, how the attitude of the Islamic boarding school in responding to the obstacles that occurred and the solution, and how effective recruitment was implemented in improving the quality of education at Pondok Pesantren Mustahafawiyah Purbabaru. The results of the study revealed that: (1) The recruitment of teaching staff at the Mustahafawiyah Purbabaru Islamic Boarding School was effective. With a good and structured process, starting from planning, organizing, implementing, to monitoring, it goes well and according to established procedures. (2) Orders and pressure from various parties are part of the obstacles that occur during the recruitment process, but can be overcome with good cooperation between the Recruitment Team and institutions and remain consistent with the agreed procedures. (3) Consistency and good cooperation that has been fostered, both between the assigned team and the institution, can carry out the recruitment process for new educators properly. So as to produce effective recruitment that produces quality educators and can assist institutions in improving the quality of education.